Assessing American and Chinese Citizen Support for Joining An International Climate Change Treaty - Flaherty, Brittany; Hermes, Hunter; Larson, Joy; Peterson, Shawn; Sikowski, Greg; Valverde, Helue Vazquez (My University, 2015)
Because meaningful climate change action will require the cooperation and participation of both China and the United States, it is increasingly important to understand what Chinese and American citizens think about this issue. Thus, a better understanding of public support for climate policy action in both countries is of great interest.
Color poster with text, tables, graphs, charts, images, and photographs.
Keywords: Chinese-American relations; Treaties; Climate change; Posters